2017
DOI: 10.1103/physrevd.96.123511
|View full text |Cite
|
Sign up to set email alerts
|

Multitracer CMB delensing maps from Planck and WISE data

Abstract: Delensing, the removal of the limiting lensing B-mode background, is crucial for the success of future cosmic microwave background (CMB) surveys in constraining inflationary gravitational waves (IGWs). In recent work, delensing with large-scale structure tracers has emerged as a promising method both for improving constraints on IGWs and for testing delensing methods for future use. However, the delensing fractions (i.e., the fraction of the lensing-B mode power removed) achieved by recent efforts have been on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 86 publications
0
43
0
Order By: Relevance
“…In addition, we expect to achieve A lens of order 0.5 from external delensing (Sherwin and Schmittfull 2015) using CIB emission and other external matter tracers. Though practical delensing demonstrations have not yet achieved such low A lens directly (Larsen et al 2016;Man-zotti et al 2017;Carron et al 2017), recent work has shown the construction of multi-tracer maps with sufficient correlation with lensing to achieve A lens ≈ 0.5 (Yu et al 2017; Planck Collaboration 2018e).…”
Section: Delensing Efficiencymentioning
confidence: 99%
“…In addition, we expect to achieve A lens of order 0.5 from external delensing (Sherwin and Schmittfull 2015) using CIB emission and other external matter tracers. Though practical delensing demonstrations have not yet achieved such low A lens directly (Larsen et al 2016;Man-zotti et al 2017;Carron et al 2017), recent work has shown the construction of multi-tracer maps with sufficient correlation with lensing to achieve A lens ≈ 0.5 (Yu et al 2017; Planck Collaboration 2018e).…”
Section: Delensing Efficiencymentioning
confidence: 99%
“…This suggests that a joint analysis could potentially give a substantial improvement to the lensing potential determination, and hence also improve the efficiency of delensing based on Planck data (Sherwin & Schmittfull 2015). A combined tracer map, including galaxy number counts from WISE in addition to the CIB and the 2015 Planck lensing map, has recently been presented over 43% of the sky by Yu et al (2017). Here we focus on the Planck-based combination of the CIB and lensing reconstructions on 60% of the sky, with similar maximum delensing efficiency, and use them to delens all four Planck CMB spectra.…”
Section: Joint Cib-cmb Lensing Potential Reconstructionmentioning
confidence: 99%
“…A lens indicates the residual lensing amplitude after delensing the lensing signal. In our analysis, we have taken A lens = 0.5 which is possible to achieve using several delensing algorithms (Simard et al 2015;Sherwin & Schmittfull 2015;Carron et al 2017;Yu et al 2017;Manzotti et al 2017;Millea et al 2017). Aτ denotes the normalization chosen to include or exclude the patchy reionization signal.…”
Section: Contamination To Tensor To Scalar Ratio and Tensor Spectral mentioning
confidence: 99%